District energy systems: Modelling paradigms and general-purpose tools. (1st December 2018) - Schweiger, Gerald; Heimrath, Richard; Falay, Basak; O'Donovan, Keith; Nageler, Peter; Pertschy, Reinhard; Engel, Georg; Streicher, Wolfgang; Leusbrock, Ingo
Abstract: District energy systems are a central element in transforming the energy system towards a low-carbon system. Simulation is regarded as key method for concept development and assessment as well as for operational optimization to address the growing complexity of these systems and to derive quantitative feedback e.g., as input for decision-support or operational processes. In this paper we present a comprehensive comparison of four widely used general-purpose modelling tools for district-scale energy systems, including a detailed discussion of modelling paradigms and co-simulation capabilities. This comparison is based on an extensive literature review, a comprehensive questionnaire that was conducted by tool and library developers, as well as a comparison of pipe model behavior of various libraries against measured data. The results including the experimental data are openly available and can support users in academia and industry with the selection of suitable modelling paradigms and associated tools and libraries.